Addictive disorders, psychiatric symptoms, and potentially traumatic events in individuals with disabilities - Marín-Navarrete, Rodrigo; Sánchez-Domínguez, Ricardo; Pérez-López, Alejandro; Saracco-Alvarez, Ricardo (Frontiers in Psychology, 2022)
Background/Objectives Individuals with disabilities (IWD) have a higher risk of potentially traumatic events (PTEs) either in childhood or adulthood, increasing the risk of suicide attempts, mental disorders, and substance use disorder. The aim of this study was to explore the association between substance use, psychiatric symptoms and suicidal behavior with PTEs. A Multisite cross-sectional study was conducted. Materials and methods The sample includes 1,098 participants with any type of disability (motor, intellectual, visual, and mixed) located in Mexico City. Traumatic events, violence, discrimination, addictive disorders, and psychiatric disorders were examined. Multivariate logistic regression models were conducted. Data was collected between September–October 2014. Results People with motor or visual disability have a higher prevalence in nicotine use disorder (NUD), generalize anxiety disorder (GAD), mayor depression disorder (MDD), want to be dead, and lifetime suicide attempts. Intellectual disability group only presents GAD and MDD. All disability groups have a high prevalence of PTEs. Verbal violence in childhood, sexual abuse, discrimination and serious accidents had a strong impact in the development of NUD, psychiatric symptoms and suicidal behavior. Conclusion These findings show the relevance of develop specific tools for detection, referral and treatment, in order to improve the mental health of people with disabilities.